A chromosome-level genome assembly of the aphid Semiaphis heraclei (Takahashi) - Xin Jiang; Ling Zhao; Jia Fan; Chunyan Chang; Xinrui Zhang; Zhuo Li; Feng Ge (Scientific Data)
Abstract The S. heraclei (Takahashi) (Hemiptera: Aphididae) is a destructive pest of cultivated insectary plant Cnidium monnieri (L.) Cuss. However, to date, no S. heraclei-related genomic information has been reported. Here, we present the first chromosomal-scale genome assembly of S. heraclei approximately 440.3 Mb with contig N50 of 81.7 Mb. Using PacBio long-read sequencing, Illumina sequencing, and Hi-C scaffolding techniques, 94.24% of the assembled sequences were successfully anchored to the four pseudochromosomes. BUSCO assessment showed a completeness score of 95.4%. The S. heraclei genome consisted of 32.02% repetitive elements and 13,983 predicted protein-coding genes. Phylogenetic analysis showed that S. heraclei was closely related to Diuraphis noxia. This high-quality genome assembly of S. heraclei will serve as a genomic resource for aphid evolution and pave the way for deciphering the tri-trophic interaction mechanisms between plants, herbivores, and natural enemies.